Belt and Road Initiative : Azerbaijan Country Case Study - Bogdan, Olena; Najdov, Evgenij (World Bank, Washington, DC, 2020)
Belt and Road Initiative (BRI), announced in 2013 and formalized in 2015, is China’s long-term commitment and aims to improve connectivity within Asia as well as between Asia and other continents via transport corridors (rail, road, maritime, air) and deeper economic, political, and cultural integration between China and the countries in Europe and Africa (National Development and Reform Commission, 2015). This study analyzes a potential impact of the BRI on Azerbaijan’s economy by focusing on (1) Azerbaijan’s connectivity and trade with the BRI economies; (2) its recent improvements in transport, power, and ICT infrastructure as part of the China, Central Asia, West Asia economic corridor; (3) its remaining connectivity gaps and challenges; and (4) potential economic effects of BRI on Azerbaijan’s trade, foreign investment, growth and welfare. Finally, the study concludes with policy implications that would mitigate the BRI risks and maximize the benefits.